editio : Internationales Jahrbuch für Editionswissenschaft (De Gruyter, 1988)
Editio serves as an international forum for textual criticism and editorial science. Articles provide information on major theoretical and methodological developments as well as the practical side of editing. Thanks to its international scope, editio facilitates a continuous debate between those subject fields that integrally involve the editing of texts.